2012
DOI: 10.3390/s120201494
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized Protein Microarray with Internal Calibration as Point-of-Care Device for Diagnosis of Neonatal Sepsis

Abstract: Neonatal sepsis is still a leading cause of death among newborns. Therefore a protein-microarray for point-of-care testing that simultaneously quantifies the sepsis associated serum proteins IL-6, IL-8, IL-10, TNF alpha, S-100, PCT, E-Selectin, CRP and Neopterin has been developed. The chip works with only a 4 μL patient serum sample and hence minimizes excessive blood withdrawal from newborns. The 4 μL patient samples are diluted with 36 μL assay buffer and distributed to four slides for repetitive measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…It is based on the light scattering properties of the biomolecules to study bound antigen-antibody complexes. The variants of optical biosensors that have been introduced so far differ in coupling agent, conjugate label, detecting signal, and transduction model to read the sensor's output [137][138][139][140][141][142][143]. The following sections discuss the general architecture of optical biosensors designed for sensitive detection of IL-6 and the signal amplification strategies adopted in each category to enhance the overall performance of the biosensor.…”
Section: Optical Biosensormentioning
confidence: 99%
“…It is based on the light scattering properties of the biomolecules to study bound antigen-antibody complexes. The variants of optical biosensors that have been introduced so far differ in coupling agent, conjugate label, detecting signal, and transduction model to read the sensor's output [137][138][139][140][141][142][143]. The following sections discuss the general architecture of optical biosensors designed for sensitive detection of IL-6 and the signal amplification strategies adopted in each category to enhance the overall performance of the biosensor.…”
Section: Optical Biosensormentioning
confidence: 99%
“…Therefore, studying the kinetics will verify the binding of analyte molecules prior to applying amplification strategies and will lead to increasing the sensitivity, accuracy and reproducibility of the assay. The same authors (Buchegger et al, 2012) earlier reported about a diagnostic microarray for neonatal sepsis. The microarray is capable of quantifying 9 various sepsis biomarkers.…”
Section: State Of the Art Of Diagnostic Microarraysmentioning
confidence: 92%
“…Further, it could help deciding the proper design of the array and its ideal processing times. Table 1 The assay processing times with the achieved limits of detection reported by Buchegger et al (Buchegger et al, 2012). Another work by Sauer and co-workers (Sauer et al, 2011) reports on the development of another sepsis diagnostic microarray.…”
Section: State Of the Art Of Diagnostic Microarraysmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept has already been proven to be feasible using a miniaturised protein microarray chip that could simultaneously quantify nine cytokines/chemokines and acute-phase proteins, including IL-6, IL-8, IL-10, tumour necrosis factor-α (TNF-α), S-100, procalcitonin, E-selectin, CRP and neopterin, with only 4 µL of serum 21. The measurement could be completed within 2.5 h using a single-step assay.…”
Section: Introductionmentioning
confidence: 99%